1999
DOI: 10.1007/s004649901174
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic gastro- and hepaticojejunostomy for palliation of pancreatic cancer

Abstract: Our preliminary experience strongly suggests that laparoscopic palliation can reduce the three major drawbacks of open bypass surgery-i.e., high morbidity, high mortality, and long hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 20 publications
2
38
0
7
Order By: Relevance
“…Laparoscopic biliary and digestive bypasses can be performed requiring highly experienced surgeons [35,36]. The debate concerning the best palliative treatment of biliary and duodenal obstruction is not resolved [37].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic biliary and digestive bypasses can be performed requiring highly experienced surgeons [35,36]. The debate concerning the best palliative treatment of biliary and duodenal obstruction is not resolved [37].…”
Section: Discussionmentioning
confidence: 99%
“…29 Minimally invasive biliary and gastrointestinal double bypass was first reported by Rhodes et al 30 in 1995, wherein they performed laparoscopic cholecystojejunostomy and gastroenterostomy. In addition, Röthlin et al 31 described the first laparoscopic double bypass with hepaticojejunostomy. In this study, they compared laparoscopic bypass cases with matched open bypass cases; results showed that laparoscopic bypass significantly decrease duration of hospital stay and reduce morphine use.…”
Section: Minimally Invasive Approach Of Biliary and Gastrointestinal mentioning
confidence: 99%
“…Many patients with periampullary cancer have symptoms associated with biliary or gastric outlet obstruction, and traditionally these patients have been managed by open bypass surgery. Recently, minimally invasive laparoscopic approaches to gastric and biliary bypass have been successfully applied, and have been shown by non-randomized comparative studies to be safer and to be associated with reduced periods of hospitalization than open surgery (Schwarz & Beger, 2000;Bergamaschi et al, 1998;Rothlin et al, 1999;Rhodes et al, 1995).…”
Section: Other Miscellaneous Pancreatectomy and Palliative Proceduresmentioning
confidence: 99%